The use of Adomian decomposition method for solving a specific nonlinear partial differential equations - Kaya, D (Belgian Mathematical Soc Triomphe, 2002)
In this paper, by considering the Adomian decomposition method, explicit solutions are calculated for partial differential equations with initial conditions. The method does not need linearization, weak nonlinearly assumptions or perturbation theory. The decomposition series analytic solution of the problem is quickly obtained by observing the existence of the self-cancelling noise terms where sum of components vanishes in the limit.
Keywords: the Adomian decomposition method; a partial differential equation; the self-cancelling noise terms